Renewal of Implementing Regulations in Minimizing Control in Limited Liability Companies Outside of Acquisitions - Pakpahan, Kartina; Tanjaya, Willy; Ferina, Wulan Me (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The problem is that the definition of